Newborn thermal care practices in two urban slums in southern Ghana: evidence from a concurrent mixed methods study - Adimazoya. E.E; Ganle. J.K.; Asampong. E.; et al (BMC Pregnancy and Childbirth, 2025)
Background In Ghana, neonatal deaths account for over 60% of infant deaths. While there are several studies examining the determinants of neonatal mortality and thermal care practices, few studies have focused on thermal care practices in urban slums. This paper examined newborn thermal care practices in two large urban slums in the southern part of Ghana. Methods The data used for this paper comes from a concurrent mixed methods cross sectional study that was conducted in two large urban slums (Ashaiman and Sodom and Gomorrah) in Accra. The quantitative survey was conducted among 279 randomly sampled mothers aged 15–49 years with live neonates 0–28 days old. Focus group discussions (14) and 13 in-depth interviews were conducted with women of reproductive age with live newborns aged 0–28 days, slum based traditional birth attendants, care givers, community leaders and public health managers who were purposively selected. Descriptive analyses was conducted to describe newborn cord care practices in the slums. Bivariate and multiple logistic regression analyses were used to assess factors associated with cord care practices at a 95% confidence level. Qualitative interviews were tape-recorded, transcribed, coded and analysed thematically. Results Prevalence of appropriate thermal care practices was 24.7%. Less than half of the neonates were dried or wiped before delivery of the placenta; 35% were wrapped, while majority of the newborns were bathed immediately or within 23 h after birth contrary to WHO recommendations. Several common newborn illnesses were reported including diarrhoea, fever, cough, acute respiratory infections, neonatal jaundice, and rashes. Mothers of newborns aged 25–34 years and those aged 35–44 years were more likely than those aged less than 25 years to provide appropriate thermal care to their newborns. The adjusted odds of receiving appropriate thermal care were higher among mothers who had skilled delivery compared to those who delivered without skilled birth attendants. Additionally, mothers of newborns residing less than 1–2 km away from the nearest health facility were more likely than those residing 3–5 km away from the nearest health facility and beyond 5 km away from the nearest health facility to provide appropriate thermal care for their newborns. Conclusion Appropriate thermal care practices in Ghana’s urban slums is low. A combination of demographic, socio economic and behavioural factors (i.e. age, marital status, education, adequate utilization of antenatal care (ANC) and skilled delivery) determine whether appropriate thermal care is provided to newborn babies. Improving thermal care practices in Ghana’s urban slums requires addressing these modifiable socio-economic and behavioural variables including strengthening ANC services, and access to routine pre- and immediate post-natal counselling for mothers. Clinical trial number Not applicable.
Research Article
Keywords: Essential newborn care; Neonate; Appropriate thermal care